Medication Adherence Barriers and Their Relationship to Health Determinants for Saudi Pediatric Dialysis Patients - Leena R. Baghdadi; Manar M. Alsaiady (MDPI AG, 2024)
Medication adherence is critical for the treatment and improved outcomes of chronic diseases. However, there is little research on the medication adherence of pediatric dialysis patients in Saudi Arabia. This study examines medication adherence barriers and their relationship to health determinants among Saudi children on dialysis, to enhance treatment success. We conducted a hospital-based, cross-sectional survey of pediatric dialysis patients using a simple random sampling technique. There is a trend of higher medication adherence for peritoneal dialysis patients compared with hemodialysis patients (36.1 ± 12.9 vs. 34.7 ± 8.3, p = 0.07). The leading barriers to medication adherence for all patients included being tired of taking the medication (score = 3.0256), not feeling like taking the medicine sometimes (score = 2.7436), bad taste (score = 2.5513), and forgetfulness (score = 2.41). Determinants of health were associated with medication adherence. Lack of education (56.4%) (some children underage for school) and chronic disease requirements (16.7%) were common barriers. After adjusting for the common confounders, the adherence scores increased significantly with increasing patient age (β = 2.378, p < 0.001), patients with working parents (β = 8.726, p = 0.011), and those living outside Riyadh (β = 19.198, p < 0.001). Medication adherence among pediatric dialysis patients is influenced by sociodemographic factors, health systems, and access to care. Evidence-based targeted interventions can increase medication adherence in this group on frequent dialysis. Future efforts should utilize systematic frameworks and digital health technologies to provide quality alternatives to improve medication adherence.